"Lutang" a documentary on the life of the Pastulan Aetas and their continuing quest for anchestral domain = "Lutang" : isang dokumentaryo tungkol sa pamumuhay ng mga Aeta sa pastulan at anf kanilang patuloy na pakikibaka para sa ancestral domain - Aganon, Celery Y.; Figueroa, Carlomagno P.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Our thesis entitled "LUTANG" : A Documentary on the Life of the Pastulan Aetas and their Continuing Quest for Ancestral Domain is a heartfelt contribution to the University and the Filipino people honoring the culture and importance of our ancestors. This production thesis has a lot stories to tell. The fifteen-minute documentary cannot compare to the eight months of interaction we had with the Aetas and our many hours of raw footage. In this study we present to the reader the indigenous community of Pastulan, a sitio straddling the mountains of Bataan with a population of 155 families, mostly Aetas. They are under the jurisdiction of the Subic Bay Metropolitan Authority. After months of pre-production and initial visits to Pastulan lat year, we finally decided to pursue the economic situation of the area as the research problem: "How can the economic situation of the Pastulan Aetas be presented in a video documentary as they continue to struggle for recognition and ancestral domain?" In this context we asked the people about the sources of economic livelihood in the village and how they lived during the American occupation of the former naval base; and how they are coping now. Presently, most of them are being employed bay the SBMA as forest rangers, eco0tour guides and maintenance personnel. Unlike before, they are now experiencing getting salaries, benfits, and other remuneration. We believe that through the methods of participants observation, interviews, and textual analyses, we were able to make a balanced, comprehensive, and relevant study. The methodology included three months of pre-production when we initially inspected Pastulan to the one month of production work. The production stage included our stay in the village. The next months were used for follow-up visits and post-production endeavors. When we talk of economic situation, it is relevant to study foru aspects: political envirment, education, family, and church. Though it seems that the Aetas are living a quite comfortable life, they continue to struggle for a real identity and a place of their own. It is in the Constitution that the indigenous peoples have a right to own their ancestral lands. Out of the 67,000 hectares of the Free =port, the Aetas consider 2,561 hectares as their own lands. This is where the conflict arises. The political environment Pastulan is in, is in disarray. How can they rightfully claim the lands when there is no clarity to what law they should follow? Presently, they have filed their claim with the National Commission on the Indigenous Peoples. They continue to negotiate with the SBMA and the municipality of Hermosa in Bataan. I tis inevitable in this country that they who have money and power, prevail. Both things the Aetas do not have. However, their remarkable determination and love their own keep them on to fight for their recognition. It is only a matter of time and history that can tell who the real victors are.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Aeta (Philippine people) -- Ancestral culture